Spectroscopic and photometric observations and analysis of compact binaries - Brink, Jaco (Department of Astronomy, 2024)
I present the results of time resolved optical spectroscopic and photometric observations of three recently discovered transient compact binary systems which comprise all three types of accretors, namely a white dwarf, neutron star and black hole. One system is a Cataclysmic Variable (CV), with an accreting white dwarf, namely 2SXPS J062339.9−265751, while two are Low-Mass X-Ray Binaries (LMXBs). One of these, Swift J1357.2−0933 is thought to contain an accreting black hole, while the other, CXOU J1109−6502, contains a neutron star and is also a Transitional Millisecond Pulsar (tMSP) candidate. All of these sources were observed as part of the Southern African Large Telescope (SALT) transient follow-up program. The CV, 2SXPS J062339.9−265751, was recently found in the eROSITA all-sky survey and was shown to be a Novalike CV system, although its true nature is not well established and photometry I present here supports a possible Intermediate Polar classification. Swift J1357.2−0933 was observed by SALT since it was discovered to be in outburst in 2019 and CXOU J1109−6502 was observed as part of a follow-up campaign, also utilizing SALT, on tMSP candidates. One major aim of this thesis is to study the time varying nature of the optical spectra of the three objects and particularly to measure the emission lines parameters and to determine the radial velocities of the systems. For 2SXPS J062339.9− 265751, spectroscopy was undertaken using the SAAO 1.9 metre telescope. In addition, time series high speed photometry, over many epochs, was also obtained and analyzed for 2SXPS J062339.9−265751, using the two SAAO 1 metre telescopes of the South African Astronomical Observatory (SAAO). The aim of the spectroscopic and photometric observations of 2SXPS J062339.9−265751 was to help understand the physical nature of the system, and determine whether it is a magnetic CV (i.e. an intermediate polar) or an over-luminous non-magnetic novalike CV. The derived Lomb- Scargle radial velocity periodograms of 2SXPS J062339.9−265751 were used to determine the orbital period of the system, which is 3.164 ± 0.036 h. This is significantly different to the photometric period determined by TESS of 3.941 ± 0.010 h which may indicate the presence of a superhump period. 2SXPS J062339.9−265751 displays some similarities to other novalike systems, such as V341 Ara and ASAS J071404+7004.3, some of which also show similar shallow broad absorption lines with strong central emission peaks. From my analysis of multiple epochs (from 1 November 2020 to 2 March 2021) of high speed photometry of 2SXPS J062339.9−265751, comprising 56.5 hours of data, I show evidence for periodicty at P = 24.905 ± 0.003 min, which I interpret as evidence that the system is a member of the intermediate polar class of magnetic CVs. For the LMXB black hole system, Swift J1357.2−0933, the observed transient blue-shifted absorption lines were analyzed to determine the radial velocity changes of the out-flowing material, previously attributed to a hot wind outflow. Persistent weak double-peaked emission lines, centred near the rest velocity, were also detected at times, most likely being produced by the accretion disk. These emission lines do not show any modulation throughout an observation, although the separation between the peaks do vary slightly from epoch to epoch. The Hα emission line is also seen to change from a broad line to showing a P Cygni profile at certain epochs. Time resolved spectra of the tMSP candidate, CXOU J1109−6502, were analysed and radial velocity measurements were determined for the Hα emission line. This emission line displayed a multi-component nature and showed dramatic changes from epoch to epoch, and even throughout a single night, from broad emission to narrow emission lines at the rest wavelength.